Advancements in the Synthesis of Building Block Materials: Experimental Evidence and Modeled Interpretations of the Effect of Na and K on Imogolite Synthesis - Escudey-Castro, A; Escudey-Castro, A; Arancibia-Miranda, N; Arancibia-Miranda, N (American Chemical Society, 2017)
The effects of Na/K substitution during the synthesis of imogolite nanotubes (NTs) were studied using a combination of structural and surface analyses. These were complemented with molecular dynamics (MD) and DFT computational models. Our results provide strong experimental evidence, obtained by various characterization techniques (FT-IR, XRD, IEP, charge measurement, and HR-TEM), showing that K changes the imogolite dimensions. In fact, in the presence of K, the nanotubes become shorter and adopt a larger diameter. Moreover, the presence of the amorphous structures associated with allophane increases, even for low K concentrations. Our results underline the complexity of imogolite synthesis engineering, highlighting their high sensitivity to the chemicals that are used during synthesis. © 2017 American Chemical Society.